Pengaruh Pertumbuhan Ekonomi, Indeks Pembangunan Manusia dan Upah Minimum Regional terhadap Tingkat Pengangguran melalui Jumlah Investasi di Kabupaten Malang - Murniati Murniati (Program Pascasarjana STIE Amkop Makassar, 2021)
Abstract The importance of investment in each region has a very large role in economic development to improve people's living standards by expanding job opportunities and directing the distribution of income evenly. This study aims to determine the direct or indirect influence between economic growth, the Human Development Index and the Minimum Wage Regional to the unemployment rate through the amount of investment in Malang Regency. This research uses path analysis with variables of economic growth, human development index, Regional Minimum Wage and unemployment rate and investment in Malang Regency. The source of the data is taken from the Central Statistics Agency of Malang Regency. The results of the analysis and discussion, it is concluded that economic growth, human development index, Regional Minimum Wage directly have no significant effect on investment. Meanwhile, economic growth and investment directly affect the unemployment rate. Meanwhile, the Human Development Index and the Regional Minimum Wage have no significant direct effect on unemployment. Malang is expected to allocate government expenditure funds to more productive sectors in the hope of expanding job opportunities. In addition, the Malang Regency government is expected to be able to establish policies that are in favor of the community, so that it is able to increase economic development so that economic growth and the human development index are even better. Keywords: Investment, Economic Growth, Regional Minimum Wage, Unemployment Rate, Path Analysis